Utilization of public or private health care providers by febrile children after user fee removal in Uganda - Rutebemberwa, Elizeus (BioMed Central, 2009)
BACKGROUND: Despite investments in providing free government health services in Uganda, many caretakers still seek treatment from the drug shops/private clinics. The study aimed to assess determinants for use of government facilities or drug shops/private clinics for febrile illnesses in children under five. METHODS: Structured questionnaires were administered to caretakers in 1078 randomly selected households in the Iganga – Mayuge Demographic Surveillance site. Those with children who had had fever in the previous two weeks and who had sought care from outside the home were interviewed on presenting symptoms and why they chose the provider they went to. Symptoms children presented with and reasons for seeking care from government facilities were compared with those of drug shops/private clinics. RESULTS: Of those who sought care outside the home, 62.7% (286/456) had first gone to drug shops/private clinics and 33.1% (151/456) first went to government facilities. Predictors of having gone to government facilities with a febrile child were child presenting with vomiting (OR 2.07; 95% CI 1.10 – 3.89) and perceiving that the health providers were qualified (OR 10.32; 95% CI 5.84 – 18.26) or experienced (OR 1.93; 95% CI 1.07 – 3.48). Those who took the febrile child to drug shops/private clinics did so because they were going there to get first aid (OR 0.20; 95% CI 0.08 – 0.52). CONCLUSION: Private providers offer 'first aid' to caretakers with febrile children. Government financial assistance to health care providers should not stop at government facilities. Multi-faceted interventions in the private sector and implementation of community case management of febrile children through community medicine distributors could increase the proportion of children who access quality care promptly.